Value orientations as a factor of mediereligious personality: empirical analysis - Kostruba, Natalia (Psychological Prospects Journal, 2022)
Purpose. The article provides an empirical analysis of the values as a factor of individual' mediareligiosity.Methods. To achieve this goal, two questionnaires were used: Schwartz's method and features of media religiosity of the individual (N.S. Kostruba). For statistical processing, we used Pearson's correlation methods, linear regression analysis, and calculated the Kruskal-Wallace H-test to compare different groups.Results. Values of preservation (security, conformity) dominate in the respondents' hierarchy of values, which involves the protection of order, stability and social harmony. Leading positions in the hierarchy have values that express the interests of the group (friendliness, conformity). Values focused solely on the interests of the individual (power and incentives) ranked last in terms of the importance of respondents. Analysis of the relationship between values and individual' mediareligiosity revealed that all components of the study phenomenon are associated with the dominance of values of tradition and security. The dominance of conformity, friendliness, universalism and achievement is also associated with a high level of mediareligiosity. We noted significant differences between the groups of respondents with different levels of media religiosity in the values of conformity, tradition, universalism, goodness, hedonism and security.Conclusions. Dominance of such value orientations as respect for traditions, friendly attitude, desire for satisfaction, as well as the desire for stability and harmony are the Factors for predicting the respondents' differentiation into groups of different levels of mediareligiosity.
Keywords: religiosity, media, values, regression analysis.